Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Pegawai PPNPN di kementerian ATR/BPN Kota Bandung - Setiawan, Sendi; Supiyadi, Dedi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
This study analyzes the influence of work environment and stress on PPNPN employees' performance at the Ministry of ATR/BPN in Bandung City. This study uses a quantitative method with a descriptive and verification approach. The population of this study was 117 PPNPN employees, while the sample taken using the Slovin technique was 90 respondents. Data was collected through a questionnaire that measured the variables of work environment, work stress, and employee performance. The results of the analysis show that the work environment has a positive and significant effect on employee performance. In contrast, work stress negatively and significantly affects employee performance. Work Environment and Work Stress jointly influence (simultaneously) the Performance of PPNPN Employees at the Ministry of ATR/BPN in Bandung City. In addition, the contribution of Work Environment and Work Stress variables to Employee Performance is 25.9%. The work environment is a variable that has a dominant influence on employee performance